The influence of the competences of the manager: Founder on the success of the organization - Ace Milenkovski; Aleksandra Stoilkovska (UTMS Journal of Economics, 2013)
The environment, where the changes are everyday occurrence and the competition continuous threat, forces the leading people in the organizations to look after everything that goes on inside the organizations, as well as everything that goes on outside of them. Thus, depending on the founder's capability, respectively the manager of the organization, the success of the organization can go up or down. The individuals that have entrepreneurial spirit, that know how to combine their knowledge, education and work experience with the successful guiding of the employees toward the goal, strengthen their business and open possibilities for its expansion. If under competence we imply to the knowledge of business, working experience and skills necessary for effective performance at the workplace, then undoubtedly the entrepreneur-founder in order to obtain the optimum knowledge for the business that he starts, previously has to build his competences through appropriate education and work experience. Herein we present working research conducted in order to prove the connection of the organization's success with the knowledge, skills and competences for the corresponding business of the organization's founder, particularly if the founder is also general manager of the organization. This research is conducted within the frames of the scientific and research activity of the University of Tourism and Management in Skopje, FYRO Macedonia. As a research sample 271 respondents - employees and 10 leaders of the companies included in the research. The leaders are managers and founders of the private companies. As a research technique questionnaire is used. Practical aim of the research was to use the results in order to create a basis for improving the performance of companies by developing the competencies of the management teams in them. One of the main conclusions of the research is: The manager-founder who starts up a business, needs to have optimum knowledge of the business i.e. appropriate education for the same, prior to working it in another company or otherwise acquired knowledge of relevant business.
Keywords: M12; 330; entrepreneur; competences; organization; manager; founder; effectiveness; efficiency